The culture of international arbitration - Kidane, Won (New York, NY : Oxford University Press, 2017)
This work offers an in-depth study of the role of culture in modern day arbitral proceedings. It contains a detailed analysis of how cultural miscommunication affects the accuracy, efficiency, fairness, and legitimacy in both commercial and investment arbitration when the arbitrators and the parties, their counsel and witnesses come from diverse legal traditions and cultures. The text provides a comprehensive definition of culture, and methodically documents and examines the epistemology of determining facts in various legal traditions and how the mixing of traditions influences the outcome.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 22, 2017).
Keywords: Arbitration (International law); Law; Laws of specific jurisdictions & specific areas of law